2016
DOI: 10.1021/acs.orglett.6b02689
|View full text |Cite
|
Sign up to set email alerts
|

Ligandless Nickel-Catalyzed Ortho-Selective Directed Trifluoromethylthiolation of Aryl Chlorides and Bromides Using AgSCF3

Abstract: A mild protocol for Ni-catalyzed trifluoromethylthiolation of aryl chlorides and bromides is described herein. The method utilizes AgSCF as an easily accessible nucleophilic trifluoromethylthiolating reagent and does not require any ligands or additives. Ortho-selectivity is achieved using a variety of directing groups such as imines, pyridines, and oxazolines for 24 examples in up to 95% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 51 publications
(21 reference statements)
0
13
0
1
Order By: Relevance
“…These in turn can be transformed with a phosphine-based catalyst system, Ni(cod) 2 /dppf, that forms [(dppf)Ni 0 (cod)] in situ. 7,18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These in turn can be transformed with a phosphine-based catalyst system, Ni(cod) 2 /dppf, that forms [(dppf)Ni 0 (cod)] in situ. 7,18 …”
Section: Introductionmentioning
confidence: 99%
“…In the context of Ni catalysis, Vicic has shown that a Ni­(cod) 2 /bipyridine system allows for functionalization of aryl iodides and selected bromides, but not aryl chlorides. These in turn can be transformed with a phosphine-based catalyst system, Ni­(cod) 2 /dppf, that forms [(dppf)­Ni 0 (cod)] in situ. , …”
Section: Introductionmentioning
confidence: 99%
“…图式 10 Ni 催化芳基、烯基类卤化物的三氟甲硫基化反应 Scheme 10 Nickel-Catalyzed coupling of ary, vinyl triflates or nonaflates with NMe 4 SCF 3 此外, 通过官能团化导向的策略, 可以更好地对底 物中的 C-Br 键以及 C-Cl 键进行活化, 从而可以更加 高效地实现相应的三氟甲硫基化转化. 不列颠哥伦比亚 大学的 Love 小组 [21] 发现, 使用不同的含氮导向基, 来 使金属镍催化剂形成五元环金属中间体, 无需配体和添 加剂的加入, 便可以在温和的条件下实现 C-Br 键、 C-Cl 键到 C-SCF 3 键的转化(Scheme 11).…”
unclassified
“…1 Therefore, trifluoromethylthiolated compounds are widely used in pharmaceuticals, agrochemicals, and functional materials. 2 Recently, considerable effort has been devoted to the development of new and efficient methods for introducing the CF 3 S group into heteroarenes with different CF 3 S sources. 3 Up to now, a broad range of important heterocycles, such as pyrrole, 4 oxindole, 5 indole, 6 indanone, 7 coumarin, 8 quinone, 9 chromone, 10 and benzofuran(thiophene), 11 have been successfully trifluoromethylthiolated using various nucleophilic, electrophilic, and radical trifluoromethylthiolating reagents.…”
Section: Introductionmentioning
confidence: 99%